The Distribution System Design Problem Applying Real Settlement Data - Buzna, Lubos (Communications - Scientific letters of the University of Zilina, 2001)
The complicated way of obtaining true values of entry parameters is a weaker part of distribution system design problem. This paper uses a continuous approximation approach to identify an optimal number of terminals. It is focused on applying real settlement data obtained from close surroundings of towns that are suitable for placing terminals. This more detailed information about settlement is used to obtain a more precise model for continuous approximation. The schemes location procedure is here used for a location of terminals.